Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Claro, vamos a resolver la expresión paso a paso con los valores dados para [tex]\(a\)[/tex], [tex]\(b\)[/tex] y [tex]\(c\)[/tex]:
Dada la expresión:
[tex]\[a \cdot 3 \cdot b - 2 \cdot a + 5 \cdot c\][/tex]
Y los valores:
[tex]\[a = -5\][/tex]
[tex]\[b = 2\][/tex]
[tex]\[c = 4\][/tex]
Sustituyamos los valores en la expresión:
[tex]\[(-5) \cdot 3 \cdot 2 - 2 \cdot (-5) + 5 \cdot 4\][/tex]
Ahora calculamos cada término:
1. Calculamos [tex]\((-5) \cdot 3 \cdot 2\)[/tex]:
[tex]\[(-5) \cdot 3 = -15\][/tex]
[tex]\[-15 \cdot 2 = -30\][/tex]
2. Calculamos [tex]\(-2 \cdot (-5)\)[/tex]:
[tex]\[-2 \cdot (-5) = 10\][/tex]
3. Calculamos [tex]\(5 \cdot 4\)[/tex]:
[tex]\[5 \cdot 4 = 20\][/tex]
Ahora sustituimos los resultados de cada término en la expresión original:
[tex]\[-30 + 10 + 20\][/tex]
Finalmente, sumamos los términos:
[tex]\[-30 + 10 = -20\][/tex]
[tex]\[-20 + 20 = 0\][/tex]
Por lo tanto, el valor numérico de la expresión es [tex]\(0\)[/tex].
Dada la expresión:
[tex]\[a \cdot 3 \cdot b - 2 \cdot a + 5 \cdot c\][/tex]
Y los valores:
[tex]\[a = -5\][/tex]
[tex]\[b = 2\][/tex]
[tex]\[c = 4\][/tex]
Sustituyamos los valores en la expresión:
[tex]\[(-5) \cdot 3 \cdot 2 - 2 \cdot (-5) + 5 \cdot 4\][/tex]
Ahora calculamos cada término:
1. Calculamos [tex]\((-5) \cdot 3 \cdot 2\)[/tex]:
[tex]\[(-5) \cdot 3 = -15\][/tex]
[tex]\[-15 \cdot 2 = -30\][/tex]
2. Calculamos [tex]\(-2 \cdot (-5)\)[/tex]:
[tex]\[-2 \cdot (-5) = 10\][/tex]
3. Calculamos [tex]\(5 \cdot 4\)[/tex]:
[tex]\[5 \cdot 4 = 20\][/tex]
Ahora sustituimos los resultados de cada término en la expresión original:
[tex]\[-30 + 10 + 20\][/tex]
Finalmente, sumamos los términos:
[tex]\[-30 + 10 = -20\][/tex]
[tex]\[-20 + 20 = 0\][/tex]
Por lo tanto, el valor numérico de la expresión es [tex]\(0\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.